Charlotte Bronte is one of the Most Famous Victorian Women Writers - Noila Ergashova Shuhrat qizi; Charos Kozokova (Journal of Innovation in Education and Social Research, 2024)
This abstract examines the enduring legacy of Charlotte Brontë, one of the most prominent Victorian women writers. It explores how her novels, notably “Jane Eyre,” defied societal norms by portraying female characters with strong wills, intellectual curiosity, and a desire for independence. The abstract delves into the themes of love, social injustice, and the complexities of female identity that permeate Brontë’s work, highlighting her unique ability to capture the emotional and psychological depth of her characters. It also acknowledges the challenges Brontë faced as a female writer during a time of limited opportunities, emphasizing her pioneering role in paving the way for future generations of women writers. This exploration of Brontë’s life and work underscores her enduring influence on literature and her continued relevance as a voice of passion and rebellion. This article defines and analyzes the most important notions in Charlotte Bronte’s novels and the specific techniques their transmission to the readers, as well as to contrast the aspects of her works with the problems of individuality.